A meta-analysis of the therapeutic effect of probiotic intervention in obese or overweight adolescents - Duan, Yuanqing; Wang, Lanping; Ma, Yan; Ning, Lei; Zhang, Xinhuan (Frontiers in Endocrinology, 2024)
Background & aims: Existing evidence on the possible effects of probiotics on obese or overweight adolescents has not been fully established. Therefore, the aim of this study was to explore the effects of probiotic supplementation on anthropometric indices, inflammatory markers and metabolic indices in obese or overweight adolescents. Methods: The literature up to March 2023 related to probiotic intervention in obese or overweight adolescents was searched and screened from multiple databases, including the CNKI（China national knowledge infrastructure）, CBM（Chinese biomedical literature database）, PubMed, EmBase, and Cochrane library databases. All randomized controlled trials using probiotic supplements in obese or overweight adolescents were included in this systematic review and meta-analysis. Results: A total of 8 studies that met the inclusion criteria were included in this study. There were 201 cases in the experimental group (probiotic treatment) and 190 cases in the control group. Compared to the control group, probiotic intervention in adolescents resulted in a decrease in body mass index, fasting blood glucose and C-reactive protein with WMD（Weighted mean difference) and 95% CI of -2.53 (-4.8 to -0.26) kg/m2, -0.80 (-1.13 to -0.47) mol/L and -0.24 (-0.43 to -0.05) mg/L, respectively. No significant changes were found in weight, waist circumference, waist-to-hip ratio, insulin, Homeostatic Model Assessment of insulin resistance, interleukin 6, tumor necrosis factor alpha and so on; however, an unfavorable elevated effect in total cholesterol, triglycerides, and low-density lipoproteins was detected with WMD and 95% CI of 0.06 (0.02 to 0.09) mmol/L, 0.18 (0.14 to 0.21) mmol/L, and 0.19 (0.18 to 0.20) mmol/L, respectively. Conclusion: According to our results, probiotic supplementation was beneficial in managing metabolic indicators such as fasting blood glucose , body mass index and inflammation-related C-reactive protein in overweight or obese adolescents. Further large scale studies are warranted to confirm present findings and to identify the effects and mechanisms to provide more precise evidence for clinical intervention.